Fiqh al-Lughah dalam Tafsir dan Ulum al-Hadits: Perannya dalam Pemahaman Makna Teks Keagamaan - Putra, Eka (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study explores the interrelation between Fiqh al-Lughah (the jurisprudence of language), Qur’anic exegesis (tafsir), and the sciences of hadith (‘Ulum al-Hadith) as three complementary disciplines in understanding Islamic religious texts. Using a qualitative library research approach, this research examines the works of M. Quraish Shihab (Tafsir al-Mishbah) and Shaykh Muhammad bin Salih al-‘Uthaymeen (Sharh Arba’in Nawawiyyah) to demonstrate how linguistic approaches are employed in the interpretation of the Qur’an and hadith. The findings reveal that Fiqh al-Lughah plays a crucial methodological role in uncovering the meanings of sacred texts through deep analysis of lafzh (lexical form), shighat (morphology), and dalalah (semantic indication). In Qur’anic exegesis, etymological and semantic analyses reveal both the spiritual and contextual depth of verses, while in hadith studies, rhetorical and syntactic analyses clarify the Prophet’s intended meanings. The novelty of this research lies in its conceptual integration of these three disciplines, which have traditionally been studied separately. This study proposes a new paradigm that views Fiqh al-Lughah not merely as a linguistic branch but as an epistemological foundation linking language, exegesis, and hadith into one coherent methodological framework. Hence, Fiqh al-Lughah emerges as an essential scientific instrument that safeguards the authenticity of Islamic texts and ensures their relevance in the modern scholarly context.